Penguatan Entrepreneurial Intention Pada Mahasiswa Berdasarkan Theory Of Planned Behavior - Ratih Indriyani; Elsa Christina (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
This study aims to determine the effect of subjectives norms, attitudes in entrepreneurship and perceived behavioral control on entrepreneurial intention among management students in Surabaya. The research was conducted by distributing questionnaires. The responses obtained were 222 data using judgmental sampling techniques which were processed using the PLS research model. The results showed that all of the proposed research hypotheses were accepted. There is an influence of subjective norms on attitudes, perceived behavioral control and entrepreneurial intention. In this study, it was also found that attitudes and perceived behavioral control had an effect on entrepreneurial intention. In addition, this study found the mediating effect of attitude and perceived behavioral control